The relationship between some regular subsemigroups of HypG2 - Weerapong Wongpinit (2018)
© 2014 Weerapong Wongpinit and Sorasak Leeratanavalee. The concept of regular subsemigroups plays an important role in the theory of semigroup. In this work, we study the relationship between some regular subsemigroups on the monoid of all generalized hypersubstitutions of type τ = (2).